Social intervention between reaction and prevention: dilemma of Social Work. A systematic review 2000-2019 - Santana Hernández, Juana D. (Cuadernos de Trabajo Social, 2021)
Abstract The purpose of Social Work is to promote changes that improve the quality of life of people and their environment. This is reflected in social intervention that mostly reacts to an emerging or existing problem that affects individuals as well as families, groups and communities. Instead, prevention does not stay in immediate care, but relies on forward-looking diagnostics about the vulnerabilities and risks of people and their environment to prevent them from suffering the effects of them or from aggravating them. With these assumptions, this study has pursued the objective of analyzing the characteristics of social intervention according to the publications of Social Work, focused on distinguishing between the two types of intervention, in response to problems already present or well trying to prevent them from resuing. For this purpose, a review of 29 articles published between 2000 and 2019 has been carried out in scientific journals. Among the results has been observed that most studies are based on experiences of reactive intervention and few are related to prevention. Recommendations for the practice and research of Social Work are raised with a preventive approach.